Gauging the scope of theft as a corruption offence: A misnomer of misappropriation of public funds? - Jean-Claude N Ashukem; Anzanilufuno Munyai (De Jure Law Journal, 2026)
Across the globe, the siphoning of public funds has become the new normal within the national social fabric and governance structures. It is increasingly common to hear and see that senior state officials are wealthier than some businessmen. While some state officials have been imprisoned for misappropriating public funds, others have evaded accountability because of their allegiance to the system. However, it is nebulous whether the appropriate criminal charge and nomenclature of the offence should be misappropriating public funds or theft. In this article, we revisit the categorisation of this offense and argue from a jurisprudential analysis in Cameroon, Kenya, Nigeria, and South Africa that it is a misnomer to qualify the offense as the misappropriation of public funds. We contend that it should be given the nomenclature it deserves: theft. Even though we acknowledge that the offense is widely referred to as the misappropriation of public funds, we posit differently and firmly so that such categorisation is sugarcoating it and enabling its perpetrators to continue the act without impunity and fear of social stigmatisation. We rely on a social-legal research approach to investigate this issue.